Delay between COVID-19 complete vaccination and SARS-CoV-2 infection among healthcare workers. Issue 23 (20th May 2022) - Saade, Anastasia; Cha, Leo; Tadié, Emilie; Jurado, Bruno; Le Bihan, Alix; Baron-Latouche, Pauline; Febreau, Christine; Thibault, Vincent; Garlantezec, Ronan; Tattevin, Pierre; Paris, Christophe
Highlights: COVID-19 complete vaccination is mandatory for healthcare workers (HCWs) Incidence density of infections increases with time from full vaccination in HCWs. Median time from vaccine completion to SARS-CoV-2 infection was 5.5 months. Using Fitted mixed Cox model, vaccines were not associated with SARS-CoV-2 infection. Abstract: Objectives: Healthcare workers (HCWs), at increased risk of coronavirus disease 2019 (COVID-19) were among the primary targets for vaccination, which became mandatory for them on September 15th, 2021 in France. In November they were confronted to the fifth COVID-19 wave despite excellent vaccine coverage. We aimed to estimate the incidence of SARS-CoV-2 infection after complete vaccination among HCWs with different vaccination schemes, and its determinants. Methods: We enrolled all HCWs in the university hospital of Rennes, France who had received complete vaccination (two doses of COVID-19 vaccine). The delay from last vaccination dose to SARS-CoV-2 infection was computed. Fitted mixed Cox survival model with a random effect applied to exposure risk periods to account for epidemic variation was used to estimate the determinants of SARS-CoV-2 infection after complete vaccination. Results: Of the 6674 (82%) HCWs who received complete vaccination (36% BNT162b2, 29% mRNA-1273, and 34% mixed with ChAdOx1 nCoV-19) and were prospectively followed-up for a median of 7.0 [6.3–8.0] months, 160 (2.4%) tested positive for SARS-CoV-2 by RT-PCR. Incidence density of SARS-CoV-2 infection after complete vaccination was 3.39 [2.89–3.96] infections per 1000 person-month. Median time from vaccine completion to SARS-CoV-2 infection was 5.5 [3.2–6.6] months. Using fitted mixed Cox regression with the delay as a time-dependent variable and random effect applied to exposure risk periods, age (P < 0.001) was independently associated with the incidence of SARS-CoV-2 infection. Vaccine schemes were not associated with SARS-CoV-2 infection ( P = 0.068). A period effect was significantly associated with the incidence of SARS-CoV-2 infection ( P < 0.001). Conclusions: In this real-world study, incidence of SARS-CoV-2 infection increases with time in fully vaccinated HCWs with no differences according to the vaccination scheme. The short delay between complete vaccination and incident SARS-CoV-2 infection highlights the need for sustained barrier measures even in fully vaccinated HCWs.